Research with pregnant women: a call to action - Margaret Olivia Little; Marisha N. Wickremsinhe (BMC, 2017)
Abstract Despite a global need for the use of medication during pregnancy, the medical research community lacks robust evidence for safety and efficacy of treatments and preventives often taken by pregnant women. Given the biological differences between pregnant women and the rest of the population, the need to gather data on the ways in which medications behave in the pregnant body is critical to the health of pregnant women and their offspring. Three ethical reasons are central to this need: 1. Pregnant women deserve access to effective treatment, 2. Pregnant women deserve access to safe treatment, and 3. Pregnant women deserve equitable access to trials carrying the prospect of direct benefit. In this paper, we introduce and frame this Supplement Issue, which presents important conference proceedings of the 2016 Global Forum on Bioethics in Research meeting held in Buenos Aires, Argentina, on the 3rd and 4th of November.